Determinan Partisipasi Petani Subak dalam Pengelolaan Desa Jatiluwih - Ni Kadek Ari Naratri; Diah Pradnyadewi T. (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the influence of tourist attractions, Subak local wisdom, environmental conservation, and accessibility on the participation of Subak farmers in the management of Jatiluwih Village, Penebel District, Tabanan Regency. Jatiluwih Village was selected as the research location because it is a tourism destination based on the Subak cultural landscape, which has been designated as a UNESCO World Heritage Site. This study employed a quantitative approach with an associative research design. The population consisted of 347 Subak farmers, with a sample of 78 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that tourist attractions, Subak local wisdom, environmental conservation, and accessibility simultaneously have a significant effect on the participation of Subak farmers. Partially, tourist attractions, Subak local wisdom, and environmental conservation have a positive and significant effect, while accessibility does not have a significant effect on the participation of Subak farmers. The Adjusted R Square value of 0.557 indicates that 55.7 percent of the variation in Subak farmers’ participation can be explained by the four independent variables, while the remaining 44.3 percent is influenced by other factors outside the research model. These findings emphasize the importance of strengthening the participation of Subak farmers in achieving a balance between tourism development, cultural preservation, and environmental conservation to maintain the sustainability of the cultural landscape and the Subak system in Jatiluwih Village.